Effects of the e-commerce on fashion luxury industries : the case of Brunello Cucinelli S.p.A. - Andreoni, Teresa (My University, 2014)
Purpose: The purpose of this study is to analyse whether luxury firms can take advantages from the adoption of the use of telematic approaches to attract customers such as the e-commerce. Traditional and more advanced marketing methods are presented. Following, challenges and opportunities are presented both from a customer’s and an enterprises’ point of view. Design/methodology/approach: The approach used is a combination of metadata concerning European luxury market, the analysis of the result of questionnaire data and the analysis of the yearly financial reports of Brunello Cucinelli S.p.A. before and after starting its e-commerce experience. Findings: The results of the analysis of the theory combined both with the outcome of the survey and the financial data suggests that indeed the use of e-commerce can indeed help firms in the luxury industry raising their profit. Research limitations/implications: Limitations were given by the unselected sample for the survey, in fact, the age range was in a student or at least young pool, therefore, I must assume that their income young workers or student strongly influenced their responses. Maybe a more selected group of interviewees would have produced a more competent outcome. Moreover, the analysis of the financial books could have been more complete with an interview of marketing and commercial manager in order to gain information that were not included in the yearly financial relations. Originality/value: This paper will bring new knowledge to the topic, as there is not much already examined and published; furthermore, the case used can become a model to analyse other similar enterprises that can match those typical characteristics of the enterprise analysed.
Keywords: marketing; e-commerce; profit; fashion luxury industry; Brunello Cucinelli.; fi=Master's Degree Programme in International Business|